Publishing modernist fiction and poetry - Jaillant, Lise (Edinburgh University Press, 2019)
Publishing houses are nearly invisible in modernist studies. Looking beyond little magazines and other periodicals, this collection highlights the importance of book publishers in the diffusion of modernism. It also participates in the transnational turn in modernist studies, demonstrating that book publishers created new markets for modernist texts in the United States, Europe and the rest of the world.